(untitled) (Polish Yearbook of International Law, 2023)
This article seeks to answer the question of how international criminal law (ICL), the 1971 Montreal Convention, and international humanitarian law (IHL) influenced the proceedings in the MH-17 case, with particular emphasis on the Dutch Prosecutors’ line of reasoning in proceedings before the District Court in The Hague (DCiTH), as well as on the judgments that the DCiTH delivered on 17 November 2022. Notably, the analysis below aims to establish whether, by refusing to grant combatant status to the defendants, the District Court acted within the limits permissible under international law, even though this Court admitted that at the moment of the MH-17’s downing, the nature of the conflict in Eastern Ukraine was an international, not a non-international, one. In conclusion, the article argues that, firstly, even though the DCiTH’s interpretation of the IHL is not free of certain flaws, the Court’s line of reasoning and the sentences it delivered are a pragmatic attempt to bridge the gap between the proper administration of justice and the efficiency of criminal proceedings in a case where an airplane downing takes place during an international armed conflict. Secondly, although most recently the European Court on Human Rights (ECtHR) took note of the MH-17 judgments, for the reasons explained in this article the scope of their potential impact on the further development of international and domestic jurisprudence is uncertain, and remains to be seen.